Evaluation of Health Literacy and its influencing factors on dormitory students of Shahid Beheshti University of Medical Sciences in Tehran - Rahman Panahi; Ali Ramezankhani; Mahmoud Tavousi; Fereshteh Osmani; Elaheh Ghazanfari; Shamsodin Niknami (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Health literacy represents the cognitive and social skills, which are used to determine the motivation and ability of individuals to acquire access and understand the methods to use the information in order to maintain and improve the health. This study aimed to assess the level of health literacy in students and identify the factors influencing it in the 2015-2016 academic year. Materials and Methods: In this cross-sectional, descriptive and analytical study, 360 students inhabiting the dormitories of Shahid Beheshti University of Medical Sciences in Tehran were randomly selected using the cluster sampling method. To collect the data, an inventory of Health Literacy for Iranian Adults was used. Data were analyzed using descriptive statistics and Chi-square test with the SPSS software version 21. Results: The mean age of the students was 22.93±4.05 years. The results showed that 9.2% (n=31) of the students had low health literacy, 27.6% (n=94) not so inadequate literacy, 42.6% (n=145) adequate health literacy, and 19.7% (n=67) excellent health literacy. Health literacy was significantly associated with gender and family income (P<0.001). Conclusions: Due to the limited level of health literacy in many students, it is necessary to design training programs commensurate with their level of health literacy and media interests.